Relation between ocean wave activity and wavefield of the ambient noise recorded in northern Poland - Simone Lepore; Marek Grad (Journal of Seismology, 2020)
The temporal and spatial variations of the wavefield of ambient noise recorded at ‘13 BB star’ array located in northern Poland were related to the activity of high, long-period ocean waves generated by strong storms in the Northern Indian Ocean, the Atlantic Ocean, and the Northern Pacific Ocean between 2013 and 2016. Once pre-processed, the raw noise records in time- and frequency-domains, and spectral analysis and high-resolution three-component beamforming techniques were applied to the broadband noise data. The power spectral density was analysed to quantify the noise wavefield, observing the primary (0.04–0.1 Hz) microseism peak and the splitting of the secondary microseism into long-period (0.2–0.3 Hz) and short-period (0.3–0.8 Hz) peaks. The beam-power analysis allowed to determine the changes in the azimuth of noise sources and the velocity of surface waves. The significant wave height, obtained by combining observed data and forecast model results for wave height and period, was analysed to characterise ocean wave activity during strong storms. The comparison of wave activity and beam-power led to distinguish the sources of Rayleigh and Love waves associated to long-period microseisms, of short-period microseisms, and of primary microseisms. High, long-period ocean waves hitting the coastline were found to be the main source of noise wavefield. The source of long-period microseisms was correlated to such waves in the open sea able to reach the shore, whereas the source of primary microseisms was tied to waves interacting with the seafloor very close to the coastlines. The source of short-period microseisms was attributed to strong storms constituted of short-period waves not reaching the coast.

The geophysical characteristic of the lower lithosphere and asthenosphere in the marginal zone of the East European Craton - Marek Grad; Jacek Puziewicz; Jacek Majorowicz; Kajetan Chrapkiewicz; Simone Lepore; Marcin Polkowski; Monika Wilde-Piórko (International Journal of Earth Sciences, 2018)

Analysis of the primary and secondary microseisms in the wavefield of the ambient noise recorded in northern Poland - Simone Lepore; Marek Grad (Acta Geophysica, 2018)

Crustal and uppermost mantle S-wave velocity below the East European Craton in northern Poland from the inversion of ambient-noise records - Simone Lepore; Marcin Polkowski; Marek Grad (International Journal of Earth Sciences, 2018)